GIAT REALISASI EKONOMI SYARIAH BERKELANJUTAN MELALUI KOMPETISI KARYA TULIS ILMIAH AKADEMIK - Afdhal Yaman; Darwis Amin; Suud Marasabessy; Arizal Hamizar; Muammar W. Maruapey; Muhammad Reza Nacikit (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Academic Scientific Writing Competition held on June 15-20, 2024, at IAIN Ambon aimed to enhance academic skills, creativity, innovation, and encourage research in the field of Islamic economics. The event consisted of several stages, including participant registration, a national seminar, desk evaluation, and the presentation of scientific papers in the semifinal and final rounds. As a result, the top three teams presented research ideas aligned with the designated topic, demonstrating high levels of enthusiasm and quality. Overall, this event successfully deepened students' understanding of Islamic economics and prepared them to actively contribute to its development in the future.